Shortest Path Finding Using Dijkstra’s Algorithm - Nurhasanah, Fitri Yani; Gata, Windu; Riana, Dwiza; Jamil, Muh.; Saputra, Surya Fajar (LPPM Universitas Islam 45 Bekasi, 2021)
In the professional work, discipline is a very important to see work ethic of an employee. Discipline has also the most important element of good behavior, both as individual and social. A problem is when people on the road in finding the shortest path in order to get to the destination on time. Finding shortest path improves workers discipline and add value to employees. With the Dijkstra’s Algorithm, we can find the shortest route. The value on the edge of a graph can be expressed as the distance between nodes (roads). Through this proposed application, it easier for us to find the shortest route in a more effective time.